Healthcare workers’ knowledge, attitudes, and practices on catheter-associated UTI prevention: influencing factors in an OB/GYN hospital - Qu, Fei; Pang, Yanyu; Wang, Mei; Liu, Xiaojie; Wang, Jing; Li, Li (Frontiers in Public Health, 2025)
BackgroundCatheter-associated urinary tract infection (CAUTI) is a leading cause of hospital-acquired infections globally, with a high prevalence in China, especially in high-risk settings like intensive care and post-operative environments. These infections are influenced by factors such as patient volume, healthcare worker training, and adherence to infection control protocols. Shanghai, as a major healthcare hub, faces unique challenges in CAUTI prevention. Healthcare workers’ knowledge, attitudes, and practices (KAP) play a crucial role in infection control, yet research on factors affecting KAP in obstetrics and gynecology remains limited. The unique patient population and specialized care protocols in these departments present specific challenges, emphasizing the need for deeper insights to enhance prevention strategies.ObjectiveThe objective was to investigate the KAP scores of healthcare workers in an OB/GYN hospital regarding CAUTI prevention and to identify the factors influencing the scores. The ultimate aim is to provide evidence for improving targeted training programs and infection control measures.Methods and participantsA cross-sectional study was conducted in an OB/GYN hospital in Shanghai, China. A total of 327 healthcare workers from various departments completed a self-administered questionnaire assessing the KAP scores related to CAUTI prevention. The questionnaire also gathered data on demographic and professional characteristics, CAUTI training frequency, leadership emphasis on infection control, and other relevant factors. Data were analyzed using univariate and multivariate analyses to identify factors significantly influencing KAP scores.ResultsDoctors scored higher than nurses in the knowledge dimension (p < 0.001), and increased training frequency was significantly associated with higher knowledge scores (p for trend < 0.001). In terms of attitudes, a longer duration of service, more frequent training, and stronger leadership emphasis were all significantly associated with more positive attitudes toward CAUTI prevention (p for trend < 0.001). Strong leadership emphasis on CAUTI prevention was also linked to improved practices (p for trend < 0.001). The multivariate analysis confirmed that factors such as professional role (doctor vs. nurse), years of service, the role of a clinical instructor, the degree of leadership emphasis, training frequency significantly influenced the scores across various KAP dimensions.ConclusionHealthcare workers’ KAP scores toward CAUTI prevention are influenced by factors such as professional role, experience, clinical instruction, leadership emphasis, and training frequency. Tailored, role-specific training and active leadership involvement are essential to improving infection control and reducing CAUTI incidence.